Analysis of Human Resource Management Strategy at Angkringan D'Legend Coffee UMKM - Frengki Putra Ramansyah; Rahmat Idhami; Adhiba Aryantie; Leny Syahnazwa Rizka (PT. Radja Intercontinental Publishing, 2025)
Analysis of human resource management (HR) strategies at Angkringan D'Legend Coffee UMKM aims to evaluate and formulate steps that can improve employee performance and business sustainability. In the context of UMKM, effective HR management is very important because it is directly related to productivity and innovation. This study uses a qualitative approach with a descriptive analysis method, which involves interviews with owners and employees as the main data sources.